A photosensitizer-inhibitor conjugate for photodynamic therapy with simultaneous inhibition of treatment escape pathways. (October 2020) - Xiao, Ming; Fan, Jiangli; Li, Miao; Xu, Feng; Zhao, Xueze; Xi, Dongmei; Ma, He; Li, Yueqing; Du, Jianjun; Sun, Wen; Peng, Xiaojun
Abstract: Photodynamic therapy (PDT) has been successfully demonstrated for anticancer treatment in vivo. However, tumor metastasis during PDT are still inevitable due to the activation of the epidermal growth factor receptor (EGFR). The current work describes the synthesis of a photosensitizer (PS)-EGFR inhibitor conjugate for PDT with simultaneous tumor metastasis inhibition. The conjugate efficiently internalized into cancer cells and generated reactive oxygen species (ROS) under light, indicating strong cytotoxicity even in hypoxic tumor environment. The presence of an EGFR inhibitor significantly inhibited cell migration and invasion. Accordingly, photoactivation of the conjugate resulted in efficient tumor growth inhibition in a 4T1 tumor-bearing mouse model and suppressed angiogenesis and tumor metastasis during PDT. Therefore, combined PDT and EGFR inhibition strategy provides a new platform for future anticancer treatment with high safety.